Short- and Long-Term Effects of United Nations Peace Operations - Sambanis, Nicholas (World Bank, 2012)
In an earlier study Doyle and Sambanis (2000) [Doyle, Michael W., and Nicholas Sambanis. 2000. "International Peacebuilding: A Theoretical and Quantitative Analysis." American Political Science Review 94(4):779–801.] showed that United Nations (UN) peace operations have made positive contributions to peacebuilding in the short term, helping parties implement peace agreements. But are the effects of UN peace operations lasting? Because the UN cannot fight wars, such operations should not be used to enforce a peace. Peacekeeping operations contribute more to the quality of the peace—that is, to securing more than the mere absence of war—than to its duration, because the effects of such operations dissipate over time. For peace to be self-sustaining, countries must develop institutions and policies that generate economic growth. UN peacebuilding lacks a strategy for fostering self-sustaining economic growth that could connect increased participation with sustainable peace. The international community would benefit from an evolution that uses economic reforms to plug the gap between peacekeeping and humanitarian assistance on the one hand and development on the other.